Computation of air chemical equilibrium composition until 30000K - Part I - Pimentel,Carlos Alberto Rocha (2011)
Abstract An algorithm was developed to obtain the air chemical equilibrium composition. The air was considered to be composed of 79% N2 and 21% O2, and the models are 5 chemical species, N2, O2, NO, N, O, and 7 chemical species, N2, O2, NO, N, O, NO+, e-, respectively. The air chemical equilibrium composition is obtained through the equilibrium constants method and it was used the Absolute Newton method for convergence. The algorithm can be coupled as a subroutine into a Computational Fluid Dynamics code, given the flow field over an atmosphere reentry vehicle where, due to high velocities, dissociative chemical reactions and air ionization can occur. This work presents results of air chemical equilibrium composition for pressures of 1, 5, 10, 50 and 100 atm in a temperature range from 300 to 30000K.